The role of environmental governance in maintaining environmental systems and achieving urban sustainability (Journal of the College of Education for Women, 2018)
The solution to the problems and challenges of the twenty-first century requires the absorption of many transformations, such as demographic change, poverty reduction, the expansion of safe and clean energy without affecting the environment, as well as reducing health risks and other transitions. It also requires greater cooperation than is possible in the current global system, because both of these constraints and challenges, even if addressed locally or nationally, are because of the potential for their transnational impact, that is, their impact on the lives of people at the global level, Which is necessary to be fully addressed unless it is guided by a comprehensive global vision. This is what environmental governance provides in terms of its international standards and mechanisms. The achievement of sustainable development depends on the achievement of environmental governance.